IMPLEMENTATION OF TPCK IN DEVELOPING LEARNING TOOLS: A CASE STUDY OF HIGH SCHOOL BIOLOGY TEACHERS IN KUWUS SUB-DISTRICT - Jeramat, Eufrasia; Ramda, Apolonia Hendrice; Nendi, Fransiskus; Jundu, Richardus; Mengeng, Elfrida Lastriana (Bio-Lectura : Jurnal Pendidikan Biologi, 2024)
TPCK is knowledge that can be used by teachers in integrating technology appropriately in the learning process based on the description of material character and pedagogical aspects. This study aims to describe the ability of Technological Pedagogical Content Knowledge (TPCK) Teachers. The method used is descriptive with a qualitative approach. The sampling technique used in this study was purposive sampling technique. Therefore, the schools used as samples in this study were SMAN I Kuwus, SMAN 2 Kuwus (Hawe) and SMAN 1 About. Data were collected by observation, interview, and documentation. Data analysis techniques used in this study include data collection, data reduction, data presentation, and conclusion drawing. Teachers' TPACK ability can be seen through the six TPACK indicators that have been previously determined. Nevertheless, there are still obstacles in implementation such as the lack of sequential application of learning model strategies and the number of devices owned by the school. This constraint is utilised by teachers to remain more creative in the teaching process.